Study on dynamics and vibration response of shield cutterhead in composite strata based on Hertz contact - Xu, Huanle; Fan, Junfei; Qian, Zhenyu; Yang, Changyun; Zhou, Xilong (Frontiers in Mechanical Engineering, 2025)
The shield cutterhead experiences eccentric loads when excavating through composite strata, leading to potential deviation of the cutterhead. This study examines the static response, modal characteristics, and vibration response of a shield cutterhead in composite strata, utilizing Hertz contact theory. The cutterhead-rock interaction is equivalently modeled as mechanical spring constraints, with contact stiffness derived from elastic contact theory for disc cutter-rock contact. The static and dynamic responses of the cutterhead under maximum thrust and rock-breaking load are analyzed using finite element simulations. Results show that moderately weathered limestone induces larger displacements compared to hard rock. Modal analysis reveals that the natural frequencies increase with rock modulus, with composite strata exhibiting intermediate values compared to the soft and hard rock. Vibration responses under rock-breaking load demonstrate rotational symmetry in uniform strata but asymmetry in composite strata, where the displacement of the upper half exceeds the lower half due to stiffness contrast. This work provides a theoretical framework for optimizing cutterhead design and tunneling parameters in heterogeneous strata.